Green Synthesis of Encapsulated Copper Nanoparticles Using a Hydroalcoholic Extract of Moringa oleifera Leaves and Assessment of Their Antioxidant and Antimicrobial Activities - Das, Prince Edwin (2020)
The synthesis of metal nanoparticles using plant extracts is a very promising method in green synthesis. The medicinal value of Moringa oleifera leaves and the antimicrobial activity of metallic copper were combined in the present study to synthesize copper nanoparticles having a desirable added-value inorganic material. The use of a hydroalcoholic extract of M. oleifera leaves for the green synthesis of copper nanoparticles is an attractive method as it leads to the production of harmless chemicals and reduces waste. The total phenolic content in the M. oleifera leaves extract was 23.0 ± 0.3 mg gallic acid equivalent/g of dried M. oleifera leaves powder. The M. oleifera leaves extract was treated with a copper sulphate solution. A color change from brown to black indicates the formation of copper nanoparticles. Characterization of the synthesized copper nanoparticles was performed using ultraviolet-visible light (UV-Vis) spectrophotometry, Fourier-transform infrared (FTIR) spectrometry, high-resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The synthesized copper nanoparticles have an amorphous nature and particle size of 35.8-49.2 nm. We demonstrate that the M. oleifera leaves extract and the synthesized copper nanoparticles display considerable antioxidant activity. Moreover, the M. oleifera leaves extract and the synthesized copper nanoparticles exert considerable anti-bacterial activity against Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Enterococcus faecalis (MIC values for the extract: 500, 250, 250, and 250 µg/mL; MIC values for the copper nanoparticles: 500, 500, 500, and 250 µg/mL, respectively). Similarly, the M. oleifera leaves extract and the synthesized copper nanoparticles exert relatively stronger anti-fungal activity against Aspergillus niger, Aspergillus flavus, Candida albicans, and Candida glabrata (MIC values for the extract: 62.5, 62.5, 125, and 250 µg/mL; MIC values for the copper nanoparticles: 125, 125, 62.5, and 31.2 µg/mL, respectively). Our study reveals that the green synthesis of copper nanoparticles using a hydroalcoholic extract of M. oleifera leaves was successful. In addition, the synthesized copper nanoparticles can be potentially employed in the treatment of various microbial infections due to their reported antioxidant, anti-bacterial, and anti-fungal activities.